Back channel negotiation : secrecy in the Middle East peace process - Wanis-St. John, Anthony (Syracuse studies on peace and conflict resolution., 2011)
Anthony Wanis-St. John "Wanis-St. John is right in focusing on back channel negotiation: it is an essential part of complex processes that cannot be understood through oversimplified frames."--ANDREA BARTOLI, George Mason University